2017
DOI: 10.1021/acsami.7b00043
|View full text |Cite
|
Sign up to set email alerts
|

Metallic Two-Dimensional Nanoframes: Unsupported Hierarchical Nickel–Platinum Alloy Nanoarchitectures with Enhanced Electrochemical Oxygen Reduction Activity and Stability

Abstract: Electrochemical oxygen reduction reaction (ORR) catalysts that have both high activities and long-term stabilities are needed for proton-exchange membrane fuel cells (PEMFCs) and metal-air batteries. Two-dimensional (2D) materials based on graphene have shown high catalytic activities, however, carbon-based materials result in significant catalyst degradation due to carbon oxidation that occurs at high electrochemical potentials. Here, we introduce the synthesis and electrochemical performance of metallic 2D n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 82 publications
(213 reference statements)
6
46
0
Order By: Relevance
“…These values are significantly higher than those of the conventional Pt/C [17] and comparable with the values reported recently for other nanoporous Pt-based alloys. [1,[20][21][22][23][24][25] Furthermore, the copper dissolution increased the specific activity of the BNP-Pt. Above all, a higher activity per ECSA (and not per mass or geometric area) for BNP-Pt after copper dissolution means that the intrinsic catalytic nature of the platinum is enhanced by the disappearance of the supporting skeletal NP-Cu, although the overpotential itself is not so different between the two BNP-Pt samples.…”
Section: Resultsmentioning
confidence: 99%
“…These values are significantly higher than those of the conventional Pt/C [17] and comparable with the values reported recently for other nanoporous Pt-based alloys. [1,[20][21][22][23][24][25] Furthermore, the copper dissolution increased the specific activity of the BNP-Pt. Above all, a higher activity per ECSA (and not per mass or geometric area) for BNP-Pt after copper dissolution means that the intrinsic catalytic nature of the platinum is enhanced by the disappearance of the supporting skeletal NP-Cu, although the overpotential itself is not so different between the two BNP-Pt samples.…”
Section: Resultsmentioning
confidence: 99%
“…33 Our group has developed bimetallic two-dimensional (2D) nanoframes that combine highly active bimetallic surface sites and a porous, carbon-free nanoarchitecture to provide oxygen electrocatalysts with improved activity and stability. 14,34,35 The 2D nanoframe structure is synthesized from thermal reduction of precious metal-decorated metal oxide nanosheets and is composed of a unique hierarchical 2D framework containing interconnected solid metallic alloy domains within a porous matrix that provides 3D molecular accessibility. We recently reported unsupported, hydrous iridium-nickel oxide 2D nanoframes exhibit 14 times higher OER mass activity than commercial IrO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The a-Ni(OH) 2 nanosheets were synthesized using a microwavesynthesis technique modified from our previously reported microwave-assisted hydrothermal method, 47,48 by adapting the protocol to a large-format microwave reactor at the Naval Research Laboratory (CEM Mars 5 Digestion Microwave System microwave reactor). In the modified synthesis, Ni(NO 3 ) 2 Á6H 2 O (3.0 g, Sigma-Aldrich) and urea (2.46 g, Sigma-Aldrich) were added to a solution of ethylene glycol (63 mL, Sigma-Aldrich) and ultrapure water (9 mL, Z18 MO cm; used for all subsequent reactions).…”
Section: Microwave Synthesis Of Ni(oh) 2 Nanosheetsmentioning
confidence: 99%
“…46 We recently reported that microwave-synthesized a-Ni(OH) 2 nanosheets serve as a high surface-area precursor to high-activity bimetallic OER electrocatalysts. 47,48 Microwave synthesis using neutral/mild pH conditions generates a-Ni(OH) 2 with a 3D flowerlike morphology 49 unlike the low surface-area aggregates characteristic of highly basic conditions. 44,45,50 Microwave synthesis has been used to synthesize a number of metal-substituted a-Ni(OH) 2 materials such as Mn/ Co-substituted a-Ni(OH) 2 as a precursor for Ni/Mn/Co oxide materials for supercapacitors, 51 3D flowerlike Co-substituted a-Ni(OH) 2 for supercapacitors, 52,53 and Al/Zn substituted a-Ni(OH) 2 .…”
Section: Introductionmentioning
confidence: 99%